2009
DOI: 10.1007/s12032-009-9195-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal toxicity and osteonecrosis of the jaw in cancer patients treated with bisphosphonates: a long-term retrospective analysis

Abstract: The low incidence of ONJ and renal toxicity indicates the safety of BP. However, prevention and early detection are still the "first-line therapy" for decreasing their occurrence further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 31 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…However, three other observational studies reported a cumulative incidence of 2.2-6.5% over 12-15 months. 62,137,144 Renal toxicity…”
Section: Osteonecrosis Of the Jawmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three other observational studies reported a cumulative incidence of 2.2-6.5% over 12-15 months. 62,137,144 Renal toxicity…”
Section: Osteonecrosis Of the Jawmentioning
confidence: 99%
“…Oh and colleagues 152 found that 23.8% of patients experienced renal toxicity over 10 months while Bonomi and colleagues 137 reported a figure of 6.5%. However, these studies had a broader definition of renal toxicity than the RCTs.…”
mentioning
confidence: 99%
“…20,21 Nephrotoxicity is another side effect in about 4% of cancer patients, especially with other nephrotoxic drugs like nonsteroidal anti-inflammatory drugs (NSAIDs). 22…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…In addition, bisphosphonates are also used for treatment of hypercalcemia in cancer patients. Nonetheless, concern has been raised that treatment with bisphosphonates may be associated with adverse events, such as atrial fibrillation,4 osteonecrosis of the jaw,5 and renal impairment 6. Cancer patients, who receive bisphosphonates in doses approximately 10 times higher than doses used to treat osteoporosis, may be at comparatively higher risk of bisphosphonate-induced adverse events.…”
Section: Introductionmentioning
confidence: 99%